Proceedings of the 5th Annual International Conference on Management Research (AICMaR 2018) 2019
DOI: 10.2991/aicmar-18.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Commodity Price on Sharia Stock Markets Volatility in Developed and Developing Countries

Abstract: This research examines the effect of commodity price on Sharia stock markets volatility in both the developed and developing countries. The current study explores the time series as analysis of economic variables and Sharia stock markets by applying the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model. The commodity price include world oil price and gold price. For representation of Sharia stock markets are Indonesia Sharia Index (ISSI), FTSE Bursa Malaysia Hijrah Sharia Index (FBMHS Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some research suggests that Sharia Stock Markets may exhibit different reactions to inflation compared to conventional stock markets, possibly due to the prohibition of prohibited goods and an aversion to excessive risktaking in Islamic financial principles (Indarwati & Widarjono, 2021;Nurhayadi & Rito, 2019). Moreover, the impact of inflation on the volatility of Sharia Stock Markets in developed and developing countries has been explored, with findings suggesting that Islamic stock indices may demonstrate greater resilience to financial crises and unique characteristics that differentiate them from conventional stock markets (Sampurna & Maronrong, 2019). While previous research results have shown varying interpretations of the impact of inflation on the Sharia Stock Market in Indonesia, with some studies stating a negative effect (Abdul Jabar & Cahyadi, 2020;Ash-shiddiqy, 2018;Fuadi, 2020;Handriani, Isnurhadi, Yuliani, & Sulastri, 2021;Masrizal, Sukmana, Al Mustofa, & Herianingrum, 2021;Nawindra & Wijayanto, 2020;Noval & Nadia, 2020;Sari & Latief, 2020), while others stating that inflation has no significant effect or even a positive effect (Anwar & A, 2020;Mahrina, 2020;Sukmayadi & Oktaviani, 2019;Umam, Ratnasari, & Herianingrum, 2019).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%
“…Some research suggests that Sharia Stock Markets may exhibit different reactions to inflation compared to conventional stock markets, possibly due to the prohibition of prohibited goods and an aversion to excessive risktaking in Islamic financial principles (Indarwati & Widarjono, 2021;Nurhayadi & Rito, 2019). Moreover, the impact of inflation on the volatility of Sharia Stock Markets in developed and developing countries has been explored, with findings suggesting that Islamic stock indices may demonstrate greater resilience to financial crises and unique characteristics that differentiate them from conventional stock markets (Sampurna & Maronrong, 2019). While previous research results have shown varying interpretations of the impact of inflation on the Sharia Stock Market in Indonesia, with some studies stating a negative effect (Abdul Jabar & Cahyadi, 2020;Ash-shiddiqy, 2018;Fuadi, 2020;Handriani, Isnurhadi, Yuliani, & Sulastri, 2021;Masrizal, Sukmana, Al Mustofa, & Herianingrum, 2021;Nawindra & Wijayanto, 2020;Noval & Nadia, 2020;Sari & Latief, 2020), while others stating that inflation has no significant effect or even a positive effect (Anwar & A, 2020;Mahrina, 2020;Sukmayadi & Oktaviani, 2019;Umam, Ratnasari, & Herianingrum, 2019).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%